High cycle fatigue assessment of steel load-carrying cruciform welded joints: an overview of recent results - song wei; Xuesong Liu (Fracture and Structural Integrity)
In this paper, high cycle fatigue failure behavior of Load-carrying Cruciform Welded Joints (LCWJ) is assessed using Strain Energy Density (SED) approach. Different analytical solutions are proposed and applied to illustrate the effects of LCWJ geometry under cycle tension and bending according to Finite Element (FE) calculation. The Notch Stress Intensity Factors (NSIF) according to the proposed analytical solutions are validated by comparing finite element data from several simulations in terms of LCWJ models, resulting in a good agreement. A bulk of experimental data taken from tests and the literature is assessed by the proposed solutions as the forms of SED, NSIF and peak stress. The results show that the SED-based analytical solutions for steel LCWJ are effective for high cycle fatigue failure analyses.